2009
DOI: 10.1016/j.vaccine.2009.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome-activating nanoparticles as modular systems for optimizing vaccine efficacy

Abstract: Innate immune system activation is a critical step in the initiation of an effective adaptive immune response; therefore, activation of a class of innate pathogen receptors called pattern recognition receptors (PRR) is a central feature of many adjuvant systems. It has recently been shown that one member of an intracellular PRR, the NLRP3 inflammasome, is activated by a number of classical adjuvants including aluminum hydroxide and saponins [1,2]. Inflammasome activation in vitro requires signaling of both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
225
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(232 citation statements)
references
References 37 publications
4
225
2
1
Order By: Relevance
“…The polymer type, the surface decoration of the particles, as well as further excipients and adjuvants all represent factors that enable the modulation of the immunological properties of a particle-based Ag delivery system (35,(46)(47)(48)(49)(50)(51)(52). In studies in which PLGA microparticles were shown to stimulate APCs associated with the release of Ags into the cytosol as consequence of destabilization of the endosomal membrane (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…The polymer type, the surface decoration of the particles, as well as further excipients and adjuvants all represent factors that enable the modulation of the immunological properties of a particle-based Ag delivery system (35,(46)(47)(48)(49)(50)(51)(52). In studies in which PLGA microparticles were shown to stimulate APCs associated with the release of Ags into the cytosol as consequence of destabilization of the endosomal membrane (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these biologically formed materials, other small particulates such as alum, silica, asbestos, and nanoparticles have been shown to result in inflammasome activation (13)(14)(15). These materials have very different physical characteristics but are small enough to be phagocytosed, and subsequent phagosome rupture has been shown to result in inflammasome activation and production of IL-1β and IL-18 (16).…”
mentioning
confidence: 99%
“…This state of "frustrated phagocytosis" leads to the disruption of lysosomes and subsequently initiates the activation of NLRP-3 receptors to form inflammasomes. 2 The delayed but robust increase in caspase-1 activity by LPSÀQDs is thus likely due to the activation of inflammasome resulting from the frustrated phagocytosis.…”
Section: Articlementioning
confidence: 99%
“…1 Inflammation can be induced by numerous exogenous agents, including airborne particles, biological aggregates, nanocrystals (quantum dots (QDs)) and lipopolysaccharides (LPS). 2 These inflammagens are recognized by macrophages and microglia and some of them bind to cell surface receptors such as Toll-like receptors (TLR). In particular, endotoxins, including LPS, bind TLR-4 and trigger receptor dimerization at the plasma membrane, which, in turn, activate signal transduction cascades to induce inflammation.…”
mentioning
confidence: 99%